The Improvement And Evaluation Of Electronic Spectacle Device Based On Obstacle Detection System For Visually Impaired Person - Mohamed Kassim, Anuar; Yasuno, Takashi; Suzuki, Hiroshi; Jaafar, Hazriq Izzuan; Mohd Aras, Mohd Shahrieel (Institute of Electrical and Electronics Engineers (IEEE), 2016)
-